Degradation of imidacloprid in a binary mixture with propylene glycol by conventional fenton process - Retumban, Joseph D.; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The degradation of the pesticide imidacloprid (lMD), (1-((6-chloro-3-pyridinyl)methyl-N-nitro- 2-imidazolidinimine), in a binary mixture with propylene glycol (PG) by conventional Fen ton process was investigated as a function of Fenton reagent's concentration and ratios in a continuously-stirred batch reactor. The decay rates of IMD were found to depend on the concentration s of hydrogen peroxide and ferrous ion. The decay efficiency of TMD decreases in the presence of PG because of the non-selectivity of hydroxyl radicals in mineralizing the organic pollutants. The removal kinetics of IMO was found to proceed in a two-stage fashion: a rapid decay followed by a much slower one. The reaction rate was fitted using pseudo-first order and pseudo second order kinetics and a mathematical model was utilized to simulate the two-stage reaction kinetics. Optimization of the degradation of IMD was also determined using experimental design methodology. Box-Behnken Design was applied to investigate the effects of initial H202 concentration, initial Fe2+ concentration and initial PG concentration on three responses: %IMD removal, %Residual H202, and %COD removal.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Imidacloprid; Pesticides -- Biodegradation